2020
DOI: 10.1002/nur.22008
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in mothers of children with epilepsy and its relation to their children's sleep

Abstract: We conducted a cross‐sectional study to examine sleep in mothers of children with epilepsy and its relation to their children's sleep. A total of 133 dyads of mothers and children with epilepsy aged 1.5–6 years were recruited between 2015 and 2018 from a children's hospital in northern Taiwan. Participating families provided demographic and health information, with children wearing an actigraphy monitor for 7 days and mothers completing sleep and depressive mood questionnaires. We found that 76 (57.1%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 40 publications
(80 reference statements)
0
21
0
Order By: Relevance
“…The CES‐D assesses both physical and mental components of depressive symptomatology, including feelings of depression, loneliness, worthlessness, helplessness, hopelessness, interpersonal difficulties, reduced energy, tiredness, appetite loss and somatic distress (Radloff, 1977). Research on maternal depression is mostly emphasized during the postpartum and early childhood period (Hunt et al, 2022; Park et al, 2022; Tsai et al, 2020b). Our findings suggest that the prevalence and severity of high depressive symptoms in child‐rearing women beyond the early childhood period may currently be underestimated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CES‐D assesses both physical and mental components of depressive symptomatology, including feelings of depression, loneliness, worthlessness, helplessness, hopelessness, interpersonal difficulties, reduced energy, tiredness, appetite loss and somatic distress (Radloff, 1977). Research on maternal depression is mostly emphasized during the postpartum and early childhood period (Hunt et al, 2022; Park et al, 2022; Tsai et al, 2020b). Our findings suggest that the prevalence and severity of high depressive symptoms in child‐rearing women beyond the early childhood period may currently be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbances in children with epilepsy are more prevalent and serious than in their healthy peers, with a prevalence rate as high as 53%–74% (Gupta et al, 2021; Winsor et al, 2021; Zhao et al, 2022). They also create a significant health and caregiving burden for parents and families (Larson et al, 2012; Tsai et al, 2020b; Yang et al, 2020). Research shows that parents of children with epilepsy have more severe symptoms of anxiety and depression, and mothers of children with epilepsy even have a seven times higher occurrence of sleep disturbances when compared with mothers of children without epilepsy (Shaki et al, 2011; Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the statements of the mothers, illness ( epilepsy seizures , toothache , fever ) and medication use were important factors disrupting the children's sleep within the scope of the children's physiological health . In the study conducted by Tsai et al (2020), the relationship between the sleep of children with epilepsy and their mothers, the disease experienced by the children and the medications they use are among the factors that disrupt their sleep. It has been determined that the child's restlessness , stress and fears affect their sleep quality negatively.…”
Section: Discussionmentioning
confidence: 99%
“…facilitate the transition to sleep of the parents in children with neurodevelopmental disabilities(Waddington et al, 2020) Hodge et al (2012). study of sleep assessment methods in children with ASD also found that peace, quiet and the dark environment make it easier for parents to sleep.4.2 | Factors that are hindering and facilitating sleep quality of children with intellectual disabilitiesAccording to the statements of the mothers, illness (epilepsy seizures, toothache, fever) and medication use were important factors disrupting the children's sleep within the scope of the children's physiological health.In the study conducted byTsai et al (2020), the relationship between the sleep of children with epilepsy and their mothers, the disease experienced by the children and the medications they use are among the factors that disrupt their sleep. It has been determined that the child's restlessness, stress and fears affect their sleep quality negatively.In another study, it was determined that health problems such as fever and toothache in children with disabilities made it difficult to sleep and prolong the transition to sleep(Kirkpatrick et al, 2019).…”
mentioning
confidence: 99%
“…Higher levels of depression and anxiety have been found among the caregivers of PWE, in comparison with the control group, in several recent reports 6,7,8 . However, although studies on sleep quality indexes among PWE have already been conducted 9,10,11,12 , research addressing the sleep quality of the caregivers of PWE is extremely rare 13,14 .…”
Section: Introductionmentioning
confidence: 99%